Caspase-11-Gasdermin D-Mediated Pyroptosis Is Involved in the Pathogenesis of Atherosclerosis - Jiang, Mengqing; Sun, Xuejing; Liu, Suzhen; Tang, Yan; Shi, Yunming; Bai, Yuanyuan; Wang, Yujie; Yang, Qiong; Yang, Qize; Jiang, Weihong; Yuan, Hong; Jiang, Qixia; et al. (Frontiers in Pharmacology, 2021)
Background Pyroptosis is a form of cell death triggered by proinflammatory signals. Recent studies have reported that oxidized phospholipids function as caspase-11 agonists to induce noncanonical inflammasome activation in immune cells. As the levels of oxidized phospholipids derived from ox-LDL are largely elevated in atherosclerotic lesions, this study sought to determine whether oxidized lipids trigger pyroptosis and subsequent inflammation in the pathogenesis of atherosclerosis. Methods and Results In our current study, after integrating transcriptomic data available from the Gene Expression Omnibus (GEO) with data from hyperlipidemic mice and ox-LDL-treated peritoneal macrophages, we discovered that caspase-4/11-gasdermin D-associated inflammatory signaling was significantly activated. Consistently, the mRNA expression of caspase-4 and gasdermin D was upregulated in peripheral blood mononuclear cells (PBMCs) from patients with coronary heart disease. In particular, the expression of caspase-4 was closely associated with the severity of lesions in the coronary arteries. An in vivo study showed that caspase-11-gasdermin D activation occurred in response to a high-fat/high-cholesterol (HFHC) diet in ApoE-/- mice, while caspase-11 deletion largely attenuated the volume and macrophage infiltration of atherosclerotic lesions. An in vitro mechanistic study showed that caspase-11-mediated inflammation occurred partly via gasdermin D-mediated pyroptosis in macrophages. Suppressing gasdermin D in HFHC-fed ApoE-/- mice via delivery of an adeno-associated virus markedly decreased lesion volume and infiltrating macrophage numbers. Conclusions Caspase-11-gasdermin D-mediated pyroptosis and the subsequent proinflammatory response in macrophages are involved in the pathogenesis of atherosclerosis. Therefore, targeting the caspase 11-gasdermin D may serve as an alternative strategy for the treatment of atherosclerosis.